A efetividade da transparência digital nas câmaras municipais de alagoas : a ação preventiva do ministério público - Santos Filho, João Batista (2022)
This dissertation presents the results of research whose main objective is to evaluate the effectiveness of the transparency of the municipal councils of Alagoas, as established by the Federal Constitution of 1988, in its art. 5, item XXXIII, and art. 37, as well as Complementary Law No. 101, of May 4, 2000 (Fiscal Responsibility Law), Law No. 12,527, of November 18, 2011 (Access to Information Law), legal provisions that ensure access to information. The research started from the results of the Transparency project in the Municipal Legislative of Alagoas, headed by the Public Ministry of Alagoas, from 2017 to 2018, in which this public body carried out an evaluation aimed at defending probity in public management, as well as promoting the participation of society in the inspection of public accounts and the adoption of measures for the full functioning of the transparency portals of public bodies. Once the term of the mentioned project was concluded, the research continued, in the period from 2019 to 2021, the same evaluation process, in order to assess the effectiveness of the transparency of the electronic portals of the municipal councils of Alagoas, since the Public Prosecutor's Office ended the inspection work to solve serious problems of lack of transparency in these institutions. Assuming a comparative character, necessary to prove the aforementioned hypothesis, the research, which is configured as a case study (SEVERINO, 2007), verified the evolution/involution of the transparency of the portals of the chambers of the 102 municipalities in Alagoas, in the years 2019 to 2021, after the execution of the said project. For this, it used the same assessment instrument used by the Public Ministry of Alagoas, namely, the metric developed by the National Strategy to Combat Corruption and Money Laundering (ENCCLA, 2015). In this way, it sought to answer the following guiding question: do transparency portals remain effective and provide access to information, in an objective, transparent and easy-tounderstand language, providing opportunities for social control and the fight against corruption? To meet the epistemological requirements, the research was based, especially, on the concepts of cyber transparency (LIMBERGER, 2016; 2008), cyber citizenship (LIMBERGER; SALDANHA, 2012), cyberspace (LÉVY, 1999; LIMBERGER; BUNCHAFT, 2016), social control (DA SILVA; SOUZA, 2017) and accountability (TAVARES; ROMÃO, 2021). In addition, it resorted to a set of laws related to the subject in question, of which the main ones are: the Federal Constitution (BRASIL, 1988), the Fiscal Responsibility Law (BRASIL, 2000) and the Access to Information Law (BRASIL, 2000). The collection of empirical data (submitted to quantitative-qualitative analysis approaches) was divided into two stages: a) survey of all city councils to verify the effective existence of portals throughout the state; b) selection of the research sample, consisting of 14 municipal councils located in the Immediate Geographical Regions of Alagoas (IBGE, 2017). It was concluded that, after 2018, with the absence of control and supervision of the Parquet of Alagoas, on the websites of the municipal councils, access to information lost effectiveness for not meeting the legal requirements, presenting a significant decrease in the quality of transparency. Thus, it is suggested the need for an attitudinal change of the Public Ministry of Alagoas, in order to design a permanent and easy to execute program to change this situation.